Analisis Keterkaitan antara Perilaku Investor dan Volatilitas Pasar - Rosyid Rosyid; Siti Asriah Immawati; Jamalus Jamalus (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Financial markets are a crucial component of the global economy, where market volatility is a primary concern for investors. This study aims to analyze the relationship between investor behavior and market volatility, focusing on how sentiment and trading behavior influence stock price dynamics. Understanding this relationship can offer valuable insights for investors and policymakers in managing market fluctuations. The study used primary data from questionnaires distributed to 400 investors. The results indicate that risk perception, investment decisions, and investor experience have a positive and significant effect on the perception of market volatility. In contrast, investor emotions, such as fear and anxiety, negatively affect their perception of volatility. The level of uncertainty investors experience significantly influences their assessment of market fluctuations. A higher perceived risk leads to a stronger tendency to perceive increased market volatility. Furthermore, the actions of investors in the stock market impact their perceptions of price changes. More active investors tend to be more aware and sensitive to market fluctuations, while those influenced by negative emotions may underestimate the extent of market changes, leading to a lower perceived volatility. Investors often ignore important market signals when trying to avoid losses, which can impact their investment decisions. Experienced investors, having encountered various market cycles, are better at handling market fluctuations. Their ability to analyze and interpret market information allows them to manage risks more effectively and optimize long-term investment returns.